Topology delimited radical‐scavenging propensity of monohydroxycinnamic acids. Issue 22 (3rd August 2020) - Borislavov, Lyuben; Velkov, Zhivko; Tadjer, Alia
Abstract: Hydroxyl derivatives of cinnamic acid, both natural and synthetic, are well‐known radical scavengers. However, not all of them feature the same radical‐scavenging propensity. Establishing the relationship between the structure of those species and their reactivity toward radicals plays a crucial role in the design of novel antioxidant pharmaceuticals founded on the same parent structure. This study aims to clarify, in a systematic and comprehensive way, the relationship between topology, geometry, and electron and spin density distribution on the one hand and the radical‐scavenging activity on the other. Different mechanisms are discussed based on the enthalpies of the possible structures generated in the process of dissociation of the OH bonds. All structures are modeled utilizing the first principles methods and accounting for the polar medium (water) at neutral pH (B3LYP/6‐311++G**/PCM). A hybrid mechanism is suggested, applicable not only to hydroxylated cinnamic acids but to phenolic acids in a polar environment in general. Abstract : The relationship between topology, geometry, and electron and spin density distribution and radical‐scavenging activity is elucidated in a systematic way. Different mechanisms are discussed based on the enthalpies of the possible structures generated in the process of dissociation of the OH bonds. All structures are modeled utilizing the first principles methods and accounting for the polar medium at neutral pH. A hybrid mechanism is suggested, applicable to phenolic acids in neutral polar environment.